Investigation of the Cooling Enhancement of a Single Crystal Diamond Heat Sink with Embedded Microfluidic Channels - Chen, D (Elsevier Ltd, 2022)
Single crystal diamond (SCD) owns superior mechanical strength, chemical stability, and the highest thermal conductivity among the well-known materials. In this work, we investigated the cooling enhancement of a cold plate made of SCD with embedded microfluidic channels. In particular, we studied the enhanced heat spreading due to conduction followed by convective dissipation of a locally heated resistor mimicking a linear hot spot within electronic chips. Experiments were carried out with various heat fluxes (9–75 W/cm2) and volumetric flow rates (0.02–0.18 ml/min) under transient state. The results showed that cold plate made of a SCD layer with embedded microfluidic channels exhibited the highest cooling effect obtained for maximum applied power density and flow rate. This indicated that combined effect of conductive spreading and convective heat transfer exhibited a significant cooling enhancement. Simulation results further support the improvement of the cooling capability due to the addition of microfluidic channels and the use of SCD as the substrate of the heat sink. © 2022 Elsevier B.V.
Keywords: Single crystal diamond; Microfluidic channels; Heat sink